2014
DOI: 10.1039/c4ra07708c
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable Bi2WO6-nanoparticle mediated one-pot multicomponent reactions in aqueous medium at room temperature

Abstract: Room temperature multicomponent reactions (MCRs) are reported using Bi2O3, BiVO4, and Bi2WO6 (nanoparticle) as heterogeneous catalysts. Among these, Bi2WO6 (5 mol%) nanoparticles showed excellent reactivity for the synthesis of functionalized dihydropyridine, polyhydroquinoline, 4H-chromene and 2-amino-4H-benzo[b]pyran derivatives in aqueous medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…Under various conditions, the Hantzsch condensation reaction of pyrazole-4-carboxaldehyde 2 with βketoester 64 and ammonium acetate or ammonia afforded the corresponding dihydropyridines 182. 131,[176][177][178][179][180][181][182][183] Similarly, N-aryl-1,4-dihydropyridines 183 were prepared by heating the 1,3-diphenyl-1H-pyrazole-4carboxaldehyde 2, ethyl acetoacetate/acetylacetone 64 and substituted anilines 184 165 Also, it was reported that the cyclocondensation of pyrazole-carboxaldehyde 2 with urea 120 or thiourea 184 120,185 and ethyl cyanoacetate 64 in the presence of sodium ethoxide 120 or potassium carbonate 185 gave the corresponding 2-oxo(thioxo)pyrimidine derivatives 185 (Scheme 79).…”
Section: Scheme 75 Synthesis Of Pyridine-3-carbonitriles 178mentioning
confidence: 99%
“…Under various conditions, the Hantzsch condensation reaction of pyrazole-4-carboxaldehyde 2 with βketoester 64 and ammonium acetate or ammonia afforded the corresponding dihydropyridines 182. 131,[176][177][178][179][180][181][182][183] Similarly, N-aryl-1,4-dihydropyridines 183 were prepared by heating the 1,3-diphenyl-1H-pyrazole-4carboxaldehyde 2, ethyl acetoacetate/acetylacetone 64 and substituted anilines 184 165 Also, it was reported that the cyclocondensation of pyrazole-carboxaldehyde 2 with urea 120 or thiourea 184 120,185 and ethyl cyanoacetate 64 in the presence of sodium ethoxide 120 or potassium carbonate 185 gave the corresponding 2-oxo(thioxo)pyrimidine derivatives 185 (Scheme 79).…”
Section: Scheme 75 Synthesis Of Pyridine-3-carbonitriles 178mentioning
confidence: 99%
“…Recent literature reveals that the 1,4‐dihydropyridine derivatives act as glycoprotein inhibitor, calcium channel blockers, antimitotic agent, anticancer and antitubercular agents . Hantzsch diethyl 1,4‐dihydro‐2,6‐dimethyl‐3,5‐pyridinedicarboxylate also act as a good source of hydride for reduction purpose, Some literature reports for dihydropyridine synthesis includes immobilized metallic phthalocyanines, hollow Fe 3 O 4 @DA‐SO 3 H as heterogeneous nano magnetic acid catalyst, Bi 2 BWO 6 nanoparticles, in situ generated HCl, etc. A number of the reported protocols to synthesize dihydropyridines requiring solvents and catalysts are not acceptable in the context of green synthesis; utilize reagents and catalysts which are either toxic or expensive and stoichiometric use of reagents with respect to reactant.…”
Section: β‐Cyclodextrin Catalyzed Organic Transformationsmentioning
confidence: 99%
“…All reagents were used without further purification and were procured from commercial sources. Melting points [30] 2 Imidazole (0.2 mmol) EtOH, reflux 1 h 86 [25] 3 TBAC (10 mol%) c Solvent-free, 100°C 35 min 82 [42] 4 Nano CP (0.01 g) d H 2 O, reflux 20 min 95 [29] 5 POPI (5 mol%) e Ball milling, ambient 13 min 97 [26] 6 ZnFe 2 O 4 NPs (40 mg) H 2 O, R.T. 3 h 93 [43] 7 Saturated K 2 CO 3 (10 ml) H 2 O, mw 3.2 min 90 [44] 8 Gel entrapped DABCO (1 g) EtOH, ambient 10 min 93 [45] 9 CAN (5 mol%) Solvent-free, 120°C 30 min 91 [46] 10 [bmim]OH (0.5 mmol) H 2 O, reflux 60 min 90 [33] 11 Na 2 CO 3 (0.1 mmol) Solvent-free, 125°C 40 min 100 [47] 12 SBA-DABCO (0.125 g) H 2 O, 80°C 25 min 87 [48] 13 5-Å MS (0.5 g) Solvent-free, MW 5 min 95 [49] 14 with TMS as an internal standard. The X-ray diffraction (XRD) was performed on Philips X-Pert (Cu-Ka radiation, λ = 0.15405 nm) in the range of 2θ = 20-80°using 0.04°as the step length.…”
Section: Generalmentioning
confidence: 99%